2020
DOI: 10.1177/2325967120959728
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Shoulder Instability in the Professional Athlete: Return to Competition, Time to Return, and Career Length

Abstract: Background: Anterior shoulder instability is a common condition in professional athletes, yet little is known about the success of surgery. Return to competition (RTC) is a metric indicative of a successful outcome for professional athletes who undergo anterior shoulder stabilization surgery. Purpose: To determine the rate of RTC, time to RTC, recurrence rate, and length of career after surgery in professional athletes who had undergone surgical treatment for anterior shoulder instability. Study Design: Case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…20 With high satisfaction rates, Blonna obtained 82% and 84% respectively. 24 Our study showed that both the IP and the HB groups showed a WOSI score of 89.98% and 87.55% respectively, without significant differences ( p 0.012).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…20 With high satisfaction rates, Blonna obtained 82% and 84% respectively. 24 Our study showed that both the IP and the HB groups showed a WOSI score of 89.98% and 87.55% respectively, without significant differences ( p 0.012).…”
Section: Discussionmentioning
confidence: 48%
“…Although these results are below those published in the literature by Dekker, with return to same sports level of 96%, and Mazzocca, 100%, the interviews with the patients showed us that 9 of the 10 patients who did not return to their sports activity corresponds to the sports restrictions imposed by the COVID-19 pandemic, where for long periods of time the sport was limited and even prohibited . 24,27 Hovelius reported in his study excellent results, a WOSI score with an average of 88% with the Latarjet technique and 79% with the Bankart arthroscopic technique. 20 With high satisfaction rates, Blonna obtained 82% and 84% respectively.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Dekker et al [ 23 ] showed no statistically significant difference in return to the competitive rates as well as the return time for athletes who had Bankart repair in comparison to the Latarjet procedure (4.6 vs 4.2 months). Ialenti et al [ 22 ] showed in their systematic review that patients who underwent Bankart repair on average took approximately one month longer to return to sports compared with those who underwent the Latarjet procedure (6.1 vs 5.3 months).…”
Section: Discussionmentioning
confidence: 99%